اثر بخشی آموزش حل مسئله برجهت گیری زندگی عاطفه مثبت و منفی و درماندگی آموخته شده زوجین ناسازگار طرح شبه آزمایشی. - فاطمه خلیلی آلاش; شهربانو دهرویه; نغمه توکلی (Arak Medical University Journal)
Introduction: The present study was conducted with the aim of investigating the effectiveness of problem solving training on life orientation, positive and negative emotions, and learned helplessness in incompatible couples in Qaemshahr city. Methods: The method of the present research was an experiment and a quasi-experimental research design with a control group. The statistical population included all couples who referred to counseling centers in Qaemshahr city in 2023. 30 couples were selected as a sample using available sampling method and randomly assigned to two experimental and control groups (15 people in each group). Then, the subjects of the experimental group received problem solving training during 8 sessions of 60 minutes. In order to collect data from life orientation questionnaires (Shier and Carver, 1994), positive and negative affect (Watson et al., 1988) and learned helplessness (Quinless and Nilsson, 1988) in two stages before and after training in both groups (experiment and control) were used. Results: The findings from the analysis of covariance test showed that problem solving training improved optimism in life orientation, increased positive emotion, and reduced learned helplessness in the tested group (p=0.05). Conclusions: According to the findings of the present research, in the field of therapy and counseling of incompatible couples, training in problem solving for the compatibility of couples and solving their conflicts; It looks very efficient and promising.